"Messy Inclusion": A Call for Dignity of Risk in Inclusive Postsecondary Education. Issue 2 (May 2022) - Bumble, Jennifer L.; Worth, Christopher R. J.; Athamanah, Lindsay S.; Rooney-Kron, Magen; Regester, April; Lidgus, Jonathan
As inclusive postsecondary education (IPSE) programs emerge and expand across the United States, many young people with intellectual and developmental disabilities (IDD) have access to higher education for the first time. To support growth and identity development, students with IDD should have access to all aspects of college life (e.g., activities, relationships, opportunities). Furthermore, students with IDD should have the freedom to take emotional, physical, and intellectual risks relative to those of their peers without disabilities. This leading edge article is written by practitioners and researchers with and without disabilities associated with the University of Missouri St. Louis IPSE program, Succeed. To center the voices of persons with disabilities, any direct quotations are in italics. In this article, we advocate for increased dignity of risk in IPSE, present a model to assess and make programmatic decisions regarding dignity of risk in IPSE, and highlight five philosophical values that guide our work toward "messy inclusion."